IMPLEMENTASI MANAJEMEN KESISWAAN DALAM MENINGKATKAN KARAKTER SISWA MELALUI GLOBAL LEADERSHIP PROGRAM DI MA DARUL FIKRI SIDOARJO - nur, nur chofifah; M. Athoiful Fanan (AL-MAFAZI: JURNAL MANAJEMEN PENDIDIKAN ISLAM, 2023)
This research is motivated by the differences that exist at MA Darul Fikri, each student has a different background and characteristics, with these differences, MA Darul Fikri implements self-development activities to express the talents and interests of students whose activities aim to improve student character. This research uses qualitative research, the main subject in the research is the principal of the MA Darul Fikri school, to collect data through observation, interviews and documentation, the data that has been obtained is then analyzed through three stages, namely data reduction, data presentation and data conclusions. The results of research on the implementation of student management in improving student character through the global leadership program at MA Darul Fikri are quite long, starting from accepting students at MA Darul Fikri to being able to run the leadership program. This program is a program created by the school to create students with leadership skills who are disciplined, tough and have a global outlook. The students' character has improved after the implementation of the program, although the improvement has not occurred completely, but the improvement has been there